2020
DOI: 10.3390/ijerph17196985
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on Mental Health: The Role of Locus on Control and Internet Use

Abstract: The true extent of the mental health implications of the COVID-19 pandemic are unclear, but early evidence suggests poorer mental health among those exposed to the pandemic. The Internet may have differential effects, by both connecting people with resources, or reinforce the constant checking of negative information. Moreover, locus of control becomes important in an uncontrollable pandemic. The current study aimed to examine whether exposure to COVID-19 would relate to greater symptoms of depression, anxiety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
103
1
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(119 citation statements)
references
References 56 publications
11
103
1
4
Order By: Relevance
“…Similar results were reported by other authors [10,92]. In addition, Sigurvinsdottir et al reported that information seeking may be associated with more symptoms of depression, anxiety or stress [93].…”
Section: Discussionsupporting
confidence: 89%
“…Similar results were reported by other authors [10,92]. In addition, Sigurvinsdottir et al reported that information seeking may be associated with more symptoms of depression, anxiety or stress [93].…”
Section: Discussionsupporting
confidence: 89%
“…However, the implication of COVID-19 mental health impact has not been clarified. The early evidence from China showed that people had reported an increased rate of anxiety, depression, stress, and psychological burden symptoms (Sigurvinsdottir et al, 2020). The increasing mental health problems due to COVID-19 were also found in European adult people (Smith et al, 2020) and the United ICoPsy States of America.…”
Section: Introductionmentioning
confidence: 99%
“…Since March 2020, Corona (SARS-CoV-2) has been a global pandemic and greatly impacts the social health system in many countries (Tasnim, Hossain, & Mazumder, 2020). The pandemic has a never-experienced impact on individual physical health in all countries, with millions of confirmed cases and thousands of mortality cases (Sigurvinsdottir, Thorisdottir, & Gylfason, 2020). COVID-19 impacts are mostly correlated to death and economic aspect.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations